(untitled) (Sindoro: Cendikia Pendidikan, 2025)
The transformation of education in the Society 5.0 era demands a paradigm shift in the role of teachers as adaptive, professional, and character-driven instructional leaders. This study aims to evaluate the effectiveness of a seminar entitled “Future Teacher Transformation Towards Professionalism and Character in Realizing Meaningful Education in the Era of 5.0” in enhancing prospective teachers’ understanding of the essential competencies and values required to meet the challenges of 21st-century education. The research employed a descriptive quantitative approach with a pre-experimental design (one group pre-test and post-test). The participants consisted of 50 students from the Teacher Professional Education (PPG) Program across four academic disciplines. Data were collected using objective test instruments administered before and after the seminar, then analyzed descriptively to determine the degree of improvement in participants’ understanding. The findings indicate a significant increase in the average scores from 67.68 (pre-test) to 90.99 (post-test), with a gain of 23.31 points. Students from the Arts and Civics Education departments showed the highest improvements, while the Guidance and Counseling department achieved the highest overall scores. These results suggest that the contextual, reflective, and value-based delivery approach used in the seminar effectively strengthened participants’ conceptual awareness of the urgency of teacher transformation. Therefore, similar professional development initiatives are recommended to be systematically integrated into teacher education programs to prepare educators who are responsive to the demands of the digital age. Transformasi pendidikan pada era Society 5.0 menuntut adanya pergeseran paradigma dalam peran guru sebagai pemimpin pembelajaran yang adaptif, profesional, dan berkarakter. Penelitian ini bertujuan untuk mengevaluasi efektivitas seminar bertema “Transformasi Guru Masa Depan Menuju Profesional, Berkarakter dalam Mewujudkan Pendidikan yang Bermakna di Era 5.0” dalam meningkatkan pemahaman calon guru mengenai kompetensi dan nilai-nilai dasar yang harus dimiliki untuk menghadapi tantangan pendidikan abad ke-21. Metode yang digunakan adalah pendekatan kuantitatif deskriptif dengan desain pre-eksperimental (one group pre-test and post-test design). Subjek penelitian terdiri atas 50 mahasiswa Program Profesi Guru (PPG) dari empat jurusan yang berbeda. Data diperoleh melalui instrumen tes objektif yang diadministrasikan sebelum dan sesudah seminar, kemudian dianalisis secara deskriptif untuk mengukur tingkat peningkatan pemahaman peserta. Hasil penelitian menunjukkan bahwa terjadi peningkatan signifikan pada rata-rata skor peserta dari 67,68 pada pre-test menjadi 90,99 pada post-test, dengan selisih kenaikan sebesar 23,31 poin. Jurusan Seni Budaya dan Pendidikan Kewarganegaraan menunjukkan peningkatan tertinggi, sedangkan jurusan Bimbingan dan Konseling mencatat skor tertinggi secara keseluruhan. Temuan ini mengindikasikan bahwa pendekatan penyampaian materi yang kontekstual, reflektif, dan berbasis karakter dalam kegiatan seminar mampu memperkuat kesadaran konseptual peserta terhadap pentingnya transformasi guru. Oleh karena itu, kegiatan serupa direkomendasikan untuk diintegrasikan secara sistematis dalam program pendidikan profesi guna menyiapkan pendidik yang relevan dengan kebutuhan zaman.